First Trials of Genome Analyses in Some Onobrychis Species using Dot-Blot and Genomic in situ Hybridization Techniques - Metin Tuna; Evren Cabi; Bozena Kolano; Gülru Yücel (Journal of Advanced Research in Natural and Applied Sciences)
The origin and genome composition of tetraploid cultivated Onobrychis viciifolia (2n = 4x = 28) were analyzed using dot-blot and genomic in situ hybridization (GISH) techniques. Dot-blot hybridization was used to find a genomic affinity between O. viciifolia and 16 diploid Onobrychis species. The hypothesis on the origin of the O. viciifolia was tested using GISH. Dot-blot analyses suggested a genomic affinity between O. viciifolia and four diploid Onobrychis species (O. kachetica, O. supina, O. pallasii, and O. vaginalis). Hybridization signals were observed on O. viciifolia chromosomes when gDNA of O. kachetica, O. supina, O. pallasi, and O. hypargyrea were used as probes. However, the observed chromosomal distribution of hybridization signals did not resemble GISH results. The observed signals colocalized with 35S rDNA or dispearse signals on all chromosomes were observed depending on the probe. Further investigations using more comprehensive and comparative analysis with both coding and repetitive DNA regions may provide a better understanding of the genome composition and evolution of O. viciifolia.